The Tiny Twig Epiphyte Erycina pusilla, a Model for Orchid Genome and Breeding Research - Bolaños Villegas, Pablo Alberto (2021)
Erycina pusilla is an orchid species from the tropics with a wide distribution in neotropical America. It is a fast-growing tiny twig epiphytic orchid and blooms constantly throughout the year. Approximately 28 MIKC/MADS-box genes from E. pusilla have been identified.Type-II MADS-box proteins (also called MIKC-domain proteins) play a crucial role during flower development, making this species an ideal orchid model for developmental studies. E. pusilla has a small diploid genome and two different alternative cytotypes have been reported, with 10 and 12 chromosomes. The karyotype evolution in Erycina is the result of processes of segment translocation and heterochromatin expansion/deletion. In order to breed new commercial orchid species, E. pusilla has been crossed with several important Oncidiinae orchids. The clone PSYP1 as E. pusilla ‘Hsingda Golden’ derived from in vitro flowering system has been granted the Plant Variety Rights in Taiwan for protection. The E. pusilla plants can also be engineered using the Agrobacterium tumefaciens strain EHA105 together with a plasmid vector carrying the CaMV 35S promoter system. The twig epiphyte E. pusilla holds enormous biotechnological and horticultural potential. It may be necessary to attempt more basic and applied research to transform the current knowledge into new Oncidium varieties with altered flower morphology, enhanced growth rate and vibrant colors.